The elephant in the other room - Roberto Veneziani; Gilbert L. Skillman (Queen Mary University of London, School of Economics and Finance, 2024)
Fabio Petri's Microeconomics for the Critical Mind (2021) is an impressive tour de force in the field of microeconomic theory. It manifests the author's command of cutting edge analytical tools, concepts, and theoretical approaches both in the mainstream and in the heterodox literature. The book aims to show that the neo-Ricardian approach, as augmented by the Keynesian/Kaleckian account of demand-constrained equilibrium, is a viable – indeed, superior – alternative to mainstream theory. While the book is effective in identifying current shortcomings of mainstream equilibrium and welfare analysis (many of which were first identified in the mainstream literature), it does not provide a rigorous demonstration that these or related difficulties are clearly avoided by the surplus approach, or that the latter is completely consistent with phenomena such as persistent unemployment. This is primarily a consequence of Petri's central distinction between "core" and "out-of-core" analysis, which offers no unified or clearly articulated basis for deriving or characterizing general equilibrium outcomes. In lieu of such foundations, Petri discusses a portfolio of analytically unconnected formal and informal narratives, some of which rely on the very theoretical constructs that he criticizes the mainstream for employing.
Keywords: D5; D6; B5; 330; economic theory; general equilibrium; stability; normative economics